Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/cjce.24489
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of homogeneous fluidization behaviour of Geldart Group A particles in gas tapered fluidized beds

Abstract: A two-dimensional gas-solid tapered fluidized bed at laboratory-scale in a homogenous fluidization regime is simulated using the computational fluid dynamics (CFD) software COMSOL 5.4. The Eulerian-Eulerian (EE) hydrodynamic model is used to predict the minimum fluidization velocity, minimum bubbling velocity, bed height, and solid volume fraction of alumina particles (in Geldart Group A) in the bed with different tapered angles.The effects of static bed heights on the minimum fluidization velocity of tapered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…In tapered beds, an additional stress exerted by the slanted walls is included in eq 4 as a new term. Thus, two new solid phase source terms are introduced as follows: 34 , , , , ) c g s s g g g (23) where k a represents the pressure drop ratio in a tapered fluidized bed to that of a columnar bed. In this work, the value of k c was set to 1 for simplicity.…”
Section: Momentum Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In tapered beds, an additional stress exerted by the slanted walls is included in eq 4 as a new term. Thus, two new solid phase source terms are introduced as follows: 34 , , , , ) c g s s g g g (23) where k a represents the pressure drop ratio in a tapered fluidized bed to that of a columnar bed. In this work, the value of k c was set to 1 for simplicity.…”
Section: Momentum Equationsmentioning
confidence: 99%
“…Kia Lashaki et al 23 studied the hydrodynamic behavior of Geldart A particles in tapered fluidized beds. Minimum fluidization velocity, minimum bubbling velocity, bed height, and solid volume fraction for various apex angles were predicted using CFD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Previous studies have optimized the gas distributor porosity and the arrangement of the pores, [7,8] and obtained that the gas-solid phase distribution is more uniform when the porosity is 0.53% and when it is arranged in a circular shape, which makes the flow more beneficial to the gas-solid phase mixing. To better investigate the uniform fluidization state of the gas-solid phase, Mansureh K. L. et al [9] investigated the flow characteristics of Geldart A particles in a conical fluidized bed at different taper degrees and suggested that a smaller time step should be used to simulate a three-dimensional conical fluidized bed. The above works have explored the fluidized bed structure only in terms of its investigation on the flow characteristics, but the effects of different models on the simulation results are not negligible, hence it is necessary to study the model sensitivity and applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings showed the highest level of agreement with the model proposed by Raste et al, as compared to other recently developed models. Kia Lashaki et al employed the Eulerian–Eulerian hydrodynamic model to forecast fundamental characteristics such as the minimum fluidization velocity, minimum bubbling velocity, bed height, and solid volume fraction of Geldart A particles within a 2D gas–solid tapered fluidized bed featuring various apex angles. The Eulerian–Eulerian (EE) or two-fluid model (TFM) treats both the gas and solid phases as interpenetrating continuous media, without limitations on particle count and without the need to individually track discrete particles.…”
Section: Introductionmentioning
confidence: 99%